Farm business planning model in the Republic of Macedonia - Simonovska, Elena (2008)
Farm record keeping in Republic of Macedonia is not recognized as one of the constructive and important management tools by the farmers. The focus of this study is to provide enterprise budget calculations for the most important vegetable crops in Republic of Macedonia, along with appropriate farm business planning model with regard to the Macedonian conditions. The study purpose is to improve the overall farm management by adapting the established farm business planning model.